Platelet-Rich Fibrin for Hard- and Soft-Tissue Healing in Mandibular Third Molar Extraction Socket - Sybil, Deborah (Ann Maxillofac Surg, 2020)
BACKGROUND: Successful management of patients reporting with extreme sensitivity in second molar after surgical extraction of deeply impacted mandibular third molar poses a big challenge to oral surgeons and periodontists worldwide. A variety of grafts, barrier membranes, and guided tissue regeneration techniques have been used postsurgically for soft- and hard-tissue formation. In the current study, platelet-rich fibrin (PRF), a second-generation platelet aggregate, was assessed for its effectiveness in promoting hard- and soft-tissue healing. OBJECTIVE: The aim of the study was to evaluate the efficacy of PRF in hard- and soft-tissue healing after extraction of mandibular third molar. MATERIALS AND METHODS: Bilateral surgical disimpaction of mandibular third molar was done on 25 patients. In every patient, randomly allocated test side received PRF and the other side acted as control. Pain, edema, tenderness, sensitivity, Sulcus Bleeding Index (SBI), Plaque Index, clinical attachment level (CAL), probing depth, and bone height were measured at different intervals for a maximum period of 6 months. RESULTS: There was a statistically significant improvement in patients' signs and symptoms of pain, tenderness, edema, and sensitivity with the use of PRF. A statistically significant improvement was seen in SBI, Plaque Index, and probing depths, while CALs and bone height were not influenced by PRF use. CONCLUSION: PRF is a very viable and useful biomaterial for soft-tissue healing and relieving patient symptoms, however, it does not help in hard-tissue healing with respect to cortical bone.